Effectiveness of Quantum Learning-Based Speech Skills Learning Using Flip Book Media - Nurwa Purnama; Yuniar Yuniar; Kemas Muhammad; Achamd Yani (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
Mastery of Arabic speaking skills (maharah kalam) poses a significant challenge for students, particularly in the context of primary education where exposure to the language is limited. Previous research has examined the use of Quantum Learning and digital media in language learning, but few have examined the impact of the combination of the two methods, particularly in teaching Arabic speaking skills. This study aims to examine the effectiveness of Quantum Learning-based maharah kalam learning using flipbook media at MI Al-Ishlah Palembang. Using a mixed method approach, this study combines quantitative data obtained from pre-test and post-test scores with qualitative interviews and observations. The data analysis process included descriptive statistics, t-test, and thematic analysis to evaluate both the effectiveness of the method and the student experience. The results showed a significant improvement in students' speaking skills, with an average increase from 72.92 in the pre-test to 89.17 in the post-test. In addition, students reported higher levels of engagement and motivation during learning. This study concludes that the integration of Quantum Learning and flipbook media is an effective strategy in improving Arabic speaking skills and can provide a more dynamic and interesting learning environment for students.